The Influence of Work Environment and Work Motivation to Employees Work Discipline at PT. Alido Poultry Shop - Yasir Maulana; Lies Diana Damayanti; Oding Syafrudin (Universitas Kuningan, 2022)
This research aim to find out the influence of work environment and work motivation to employees work discipline at PT. Alido poultry shop . The population in this study were employees of PT. Alido Poultry Shop Kuningan. Research using a questionnaire with a sample of 50 respondents with an interval scale. The research method used is using saturated sampling which is a sampling technique, if all members of the population are sampled. Test the validity of the instrument using the correlation technique, while the reliability test uses the Cronbach's Alpha coefficient. The technique used is quantitative data analysis technique. The results of the study indicate that the work environment has a positive and significant effect and also has the greatest influence on employee work discipline. Work Motivation has a positive and significant influence on Employee Work Discipline. Work Environment and Work Motivation together using the f test shows that these variables have a positive and significant influence on Employee Work Discipline.